2018
DOI: 10.21470/1678-9741-2018-0019
|View full text |Cite
|
Sign up to set email alerts
|

When is the Best Time for Corrective Surgery in Patients with Tetralogy of Fallot between 0 and 12 Months of Age?

Abstract: ObjectiveTo identify the best time for corrective surgery of tetralogy of Fallot (TF) in children aged 0-12 months and to report the most frequent complications during the first 3 years postoperatively.MethodsSystematic review of studies published between 2000 and 2017 on corrective surgery for TF. Articles were selected through search of electronic databases (PubMed, SciELO, Scopus, Lilacs, Google Scholar, and Cochrane). Length of stay in intensive care unit, duration of mechanical ventilation, and peri/posto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
10

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 33 publications
0
9
0
10
Order By: Relevance
“…The best age for performing definitive corrective surgery for ToF is still a topic of discussion but there is a world-wide tendency to perform Fallot corrections as early as six months [34]. In a previous study by Li et al [8] lower strain values of the RV were found in patients operated at an age above 12 months of age as compared to an age below 12 months.…”
Section: Relation To Clinical Parametersmentioning
confidence: 98%
“…The best age for performing definitive corrective surgery for ToF is still a topic of discussion but there is a world-wide tendency to perform Fallot corrections as early as six months [34]. In a previous study by Li et al [8] lower strain values of the RV were found in patients operated at an age above 12 months of age as compared to an age below 12 months.…”
Section: Relation To Clinical Parametersmentioning
confidence: 98%
“…Ao que tudo indica, ela tem leve prevalência no sexo feminino e sua causa ainda não é bem definida 2,7 . Consiste em uma série de alterações anatômicas que resultam em consequências tanto fisiológicas como patológicas 6,9 .…”
Section: Resultsunclassified
“…Tetralogy of Fallot is one of the most prevalent cyanotic congenital heart diseases, presenting a poor prognosis without surgical treatment ( 4 ). Definitive corrective surgery is the best option for patients with ToF.…”
Section: Discussionmentioning
confidence: 99%
“…From a genetic perspective, the etiology of ToF is a combination of genetics and environment, with a familial recurrence risk of 3% ( 2 ). Without timely surgical treatment, only 10% of patients could survive beyond the age of 20, others die before adulthood due to the consequences of secondary myocardial hypertrophy and heart failure caused by chronic hypoxia ( 4 ). Primary repair in the 1st year of life is the most prevalent strategy, with definitive corrective surgery as the best approach ( 5 ).…”
Section: Introductionmentioning
confidence: 99%